A gazdasági, műszaki fejlődés hatása a szerződések jogára - Török, Éva (Jelenkori Társadalmi és Gazdasági Folyamatok, 2012)
In this communication, the effects of the economical, moreover the technical growth on the contract law is presented comprehensively. The traditional framework of the civil law contracts has been broken by the development and phenomena of market economy in our country. Furthermore the legal milieu has to go by the changed demands of the economic operators. As results of the business-like management, the large investments as well as the cross-border transactions formed more and more novel, the so-called atypical contracts in the Hungarian law. New contracting methods are linked with the technological evolution. At first, the pre-prepared model contracts came into view by the development of the mass production, additionally the digital environment vivified the possibilities of electronically created contracts. The contract law legislation of the European Union had a significant effect on the discussed field also.